EFFECT OF CHROMIUM AND MANGANESE METAL ON BIOMASS AND GROWTH RATE OF SOME PULSES - K. V. SONI; B. D. BHUVA (International Journal of Pharma and Bio Sciences, 2015)
Metals are essential micro molecules required by living cell for biochemical reactions. Several metals are essential and useful to cells while few show adverse effects on living forms. Chromium and manganese are commonly counted as important metals to plant cells but sometimes their higher concentration is harmful to plant cells. Present study focused on of effects of chromium and manganese on biomass and growth rate of three widely cultivated pulses i.e. Glycine max, Vigna unguiculata and Vigna aconitifolia. It was found that higher concentration of manganese showed reduction in biomass and growth rate of all three investigated plants. However, chromium poses adverse effect on biomass and growth rate of experimental plants even at low concentrations.